SS-4 is a highly selective small molecule inhibitor of STAT3 tyrosine phosphorylation that potently inhibits GBM tumorigenesis in vitro and in vivo. (1st May 2022) - Wang, Yinan; Yang, Chuanhe; Sims, Michelle M.; Sacher, Joshua R.; Raje, Mithun; Deokar, Hemantkumar; Yue, Peibin; Turkson, James; Buolamwini, John K.; Pfeffer, Lawrence M.
Abstract: Glioblastoma (GBM) is a highly aggressive cancer with a dismal prognosis. Constitutively active STAT3 has a causal role in GBM progression and is associated with poor patient survival. We rationally designed a novel small molecule, SS-4, by computational modeling to specifically interact with STAT3. SS-4 strongly and selectively inhibited STAT3 tyrosine (Y)-705 phosphorylation in MT330 and LN229 GBM cells and inhibited their proliferation and induced apoptosis with an IC50 of ∼100 nM. The antiproliferative and apoptotic actions of SS-4 were Y-705 phosphorylation dependent, as evidenced by its lack of effects on STAT3 knockout (STAT3 KO ) cells or STAT3 KO cells that overexpressed a phospho-Y705 deficient (STAT3Y705F) mutant, and the recovery of effects when wild-type STAT3 or a phospho-serine (S)727 deficient mutant was expressed in STAT3 KO cells. SS-4 increased the expression of STAT3 repressed genes, while decreasing the expression of STAT3 promoted genes. Importantly, SS-4 markedly reduced the growth of GBM intracranial tumor xenografts. These data together identify SS-4 as a potent STAT3 inhibitor that selectively blocks Y705-phosphorylation, induces apoptosis, and inhibits growth of human GBM models in vitro and in vivo. Highlights: Rationally designed novel small molecule inhibitor of STAT3, SS-4. SS-4 potently inhibited STAT3 tyrosine phosphorylation in GBM cells. SS-4 inhibited GBM cell proliferation, cell invasion and cell survival. SS-4 increased STAT3-regulated tumor suppressor and decreased promoting genes. SS-4 has anticancer activity in an orthotopic animal model of GBM.